2018
DOI: 10.1080/17531055.2018.1547259
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking publics in Africa in a digital age

Abstract: The digital transformations taking place across the African continent present an urgent need for fresh thinking in the study of publics. This introduction lays out the impetus and contribution of this Special Issue to such a rethinking of the study of publics in Africa. Following in the footsteps of a wider body of scholarship, we draw on Africa's pasts and present in order to move beyond the limiting assumptions, histories and languages that are embedded within Western scholarship on publics. We make the case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…Across Somalia, Ethiopia, Sudan, Uganda, Tanzania, Kenya, South Africa, Rwanda and Zimbabwe, varied roles are played by WhatsApp groups convening citizens for collective action. 23 24 Digital mobilisation has highlighted important implications for breaking free of Western frames of reference that may limit engagement.…”
Section: The Future Is Collectivementioning
confidence: 99%
“…Across Somalia, Ethiopia, Sudan, Uganda, Tanzania, Kenya, South Africa, Rwanda and Zimbabwe, varied roles are played by WhatsApp groups convening citizens for collective action. 23 24 Digital mobilisation has highlighted important implications for breaking free of Western frames of reference that may limit engagement.…”
Section: The Future Is Collectivementioning
confidence: 99%
“…It is noted that the news media technologies and platforms have provided us with both opportunities and challenges. The opportunities are how we make this cyberspace more pluralistic and democratic for the discussion and participation of digital publics, and challenges are how we ensure that this democratic cyberspace is available to gratify the needs of the digital public [12].…”
Section: The Emergence Of Digital Public and Their Needsmentioning
confidence: 99%
“…This incident in particular had a chilling effect on the digitally connected public, as it demonstrated that young and seemingly unthreatening bloggers could end up in jail (Gagliardone, 2016; Human Rights Watch (HRW), 2015). The following national elections in Ethiopia in 2015 took place in an environment of digital apathy and tame online discussion (Gagliardone et al, 2019; Srinivasan et al, 2019).…”
Section: The Ethiopian Media Spherementioning
confidence: 99%